Mother–child communication about possible cancer recurrence during childhood cancer survivorship. Issue 4 (3rd December 2020) - Murphy, Lexa K.; Heathcote, Lauren C.; Prussien, Kemar V.; Rodriguez, Erin M.; Hewitt, Jackson A.; Schwartz, Laura E.; Ferrante, Amanda C.; Gerhardt, Cynthia A.; Vannatta, Kathryn; Compas, Bruce E.
Abstract: Objective: Providing opportunities to communicate about possible cancer recurrence may be adaptive for youth in remission, yet parents may experience difficulty guiding discussions related to fears of cancer recurrence (FCR). This study aimed to characterize mother–child discussions about potential cancer recurrence during post‐treatment survivorship and to determine predictors of maternal communication. Methods: Families ( N  = 67) were recruited after the child's initial cancer diagnosis (age 5–17 years) and mothers self‐reported their distress (post‐traumatic stress symptoms; PTSS). During survivorship 3–5 years later, mothers were video‐recorded discussing cancer with their children. Presence and length of discussion about potential cancer recurrence, triggers for FCR, expressed affect, and conversational reciprocity were examined. Hierarchical regressions were used to assess maternal PTSS near the time of cancer diagnosis and child age as predictors of maternal communication. Results: Three‐quarters of dyads spontaneously discussed risk for or fears about cancer recurrence; mothers initiated the topic more frequently than their children. Dyads discussed internal (bodily symptoms) and external (medical, social) triggers of FCR. Higher maternal PTSS at diagnosis predicted significantly lower levels of maternal positive affect ( β  = −0.36, p  = 0.02) and higher levels of maternal negative affect ( β  = 0.30, p  = 0.04) during discussion of recurrence 3–5 years later. Older child age significantly predicted higher levels of maternal negative affect ( β  = 0.35, p  = 0.02). Higher maternal PTSS at diagnosis predicted shorter discussions about recurrence for younger children ( β  = 0.27, p  = 0.02). Conclusions: Understanding predictors and characteristics of mother–child discussions about recurrence can guide family‐based FCR interventions, particularly those promoting communication as a supportive tool. Both maternal PTSS and child age are important to consider when developing these interventions.